HAZARDOUS CHEMICALS’ SAFETY MEASURES AND AWARENESS IN PUBLIC AND PRIVATE HOSPITAL LABORATORIES IN BURAYDAH, AL QASSIM - Alshammari, Shuaa Z; Irfan, Uma M (LIFE: International Journal of Health and Life-Sciences, 2018)
Medical laboratories in general operate with various hazardous chemicals. The storage, usage and knowledge about the hazardous chemicals are important aspects of safety measures employed in Medical Laboratories. This comparative study explores the differences in safety measures and knowledge of chemical safety among laboratory employees in Public (PBL) and Private (PRL) Hospital medical laboratories. This cross-sectional study was conducted in randomly selected Public and Private Hospital laboratories in Buraydah, Al Qassim, in 2013. The study was designed to: estimate the proportion and types of the hazardous chemicals used in the laboratories with a chemicals list; to assess safety measures currently being practiced with a standard chemical safety measures checklist; and to assess laboratory employee awareness on chemical safety with an interview schedule. Public Laboratories showed better results as compared to the Private Laboratories, in that their employees were more disciplined in wearing Personal Protection Equipment, and the laboratory was active in managing chemical accidents and its consequences. Whereas the Private Laboratories had better results on four aspects, namely: better storage and handling of hazardous chemicals; neutralizing hazardous chemicals; better precautions established for hazardous chemical use; and better assessment of chemical toxicity, as compared to the Public Laboratories. There were subtle differences between the Public and Private medical laboratories on chemical safety measures. The differences recorded were mainly in storage and handling of hazardous chemicals; the proportion and types of hazardous chemicals used; employee discipline on chemical safety measures; assessment of chemical toxicity; and in managing chemical accidents in the laboratories.